Analisis Metode dalam Pengemasan Obat Primer dan Sekunder di Industri Farmasi - Fayza Nindya Nur’Assyfa; Nia Kusumadewi; Nor Latifah (Vitamin : Jurnal ilmu Kesehatan Umum, 2025)
Optimization of primary and secondary packaging is crucial for the quality and efficiency of drug production. The drug packaging process consists of primary packaging that is in direct contact with the product and secondary packaging that provides additional protection and important information. This study aims to analyze various methods applied in pharmaceutical packaging to assess the effectiveness of Lean Manufacturing (VSM), Single Minute Exchange of Dies (SMED), and Overall Equipment Effectiveness (OEE). This study shows that VSM significantly reduces the time of secondary packaging activities. SMED reduces the lead time of primary packaging analysis by 58.06%. Meanwhile, OEE analysis of primary packaging identified high set-up/adjustment as the main cause of losses. The importance of implementing structured methods to increase productivity, reduce waste, and ensure a more efficient and effective packaging process in the pharmaceutical industry, contributing to improving product quality and safety.